Peningkatan Pemahaman Orang Tua dalam Mengidentifikasi Terjadinya Tindakan Kekerasan Seksual Terhadap Anak di Kecamatan Pauh - Fachrina Fachrina; Yulkardi Yulkardi; Afrizal Afrizal (Warta Pengabdian Andalas, 2021)
A sexual violence against children can occur anywhere, either in the family environment (private space) or in the neighborhood, work environment, school and other public spaces. Where the perpetrator is the majority of people closest to the victim, example father, uncle, brother or neighboor. For this reason, an increase in parental understanding in identifying the occurrence of sexual violence against children is needed because it is a serious problem that has a negative impact. The purpose of this service activity was to motivate and encourage parents to have a correct understanding in the management of sexual violence against children. It was held by distributed the information to target home and followed by discussion and consultation virtually. The target audience is parents in the Cupak Tangah sub-district who have children less than 17 years of age. This activity has been the parent’s awareness in the occurrence of acts of sexual violence against children.